Unvealing Sex Addiction Among Child Victims of Sexual Crimes In Indonesia - Syarifah Ema Rahmaniah; Elyta Elyta; Hasan Amutahar; Nikodemus Niko; Nurul Amira Fitriani; Muhammad Musa Hasni; Desita Sari (Cita Konsultindo Research Center, 2023)
This research aims to unveil sex addiction behavior among child victims of sexual crimes by conducting a critical analysis of the government's management of preventing child sexual crimes. The location of this research was West Kalimantan Province Indonesia. The primary data collection technique involved in-depth interviews with 5 child victims of sexual vioThis research aims to unveil sex addiction behavior among child victims of sexual crimes by conducting a critical analysis of the government's management of preventing child sexual crimes. The location of this research was West Kalimantan Province Indonesia. The primary data collection technique involved in-depth interviews with 5 child victims of sexual violence as well as focus group discussions with the child protection commission, Rumah AMAN managers, literacy activist, and the parents of the child victims. Subsequently, the research results indicated an increase in cases of sexual violence against children in various forms, such as pornography, prostitution, and sex addiction. The second finding concerned efforts to prevent sexual violence by the West Kalimantan provincial government. This involved the issuance of policies and the provision of education and sensitization through social media via the Indonesian Anti-Defamation Society (MAFINDO). In order to deal with child victims of violence, the government established the Regional Child Protection Commission (KPAD) in collaboration with Rumah AMAN. The third finding discussed the impact of sex crimes on children, namely sex addiction, sexually transmitted infections, an increase in the number of abortions, and damage to mental health. The fourth finding was conducting media literacy education, fostering the blocking of pornographic sites, and providing shelter through the Penta helix strategy by the draft government, society, and community (MAFINDO). Consequently, this research can provide knowledge about the handling tactic and strategy that can be used to deal with cases of child sex crimes.lence as well as focus group discussions with the child protection commission, Rumah AMAN managers, literacy activist, and the parents of the child victims. Subsequently, the research results indicated an increase in cases of sexual violence against children in various forms, such as pornography, prostitution, and sex addiction. The second finding concerned efforts to prevent sexual violence by the West Kalimantan provincial government. This involved the issuance of policies and the provision of education and sensitization through social media via the Indonesian Anti-Defamation Society (MAFINDO). In order to deal with child victims of violence, the government established the Regional Child Protection Commission (KPAD) in collaboration with Rumah AMAN. The third finding discussed the impact of sex crimes on children, namely sex addiction, sexually transmitted infections, an increase in the number of abortions, and damage to mental health. The fourth finding was conducting media literacy education, fostering the blocking of pornographic sites, and providing shelter through the Penta helix strategy by the draft government, society, and community (MAFINDO). Consequently, this research can provide knowledge about the handling tactic and strategy that can be used to deal with cases of child sex crimes.